Online learning with multi-representation worksheets for oral and written communication skills on light reflecting material - Putri Mardiana Sari; Kartini Herlina; Abdurrahman Abdurrahman (CV FOUNDAE, 2022)
To fulfill 21st-century skills, one of the skills needed is communication skills in oral and written form. This study aims to practice oral and written skills through learning multi-representation worksheets on light-reflecting material. By using the experimental method, namely one group pretest-posttest design. The sample in this study used a purposive sampling technique, which is the sample was selected based on certain reasons with a total of 36 students. The research instrument is a questionnaire of oral and written communication skills that have been tested for validity and reliability. The results of the study stated that the learning process following the needs, and representation activities in the learning process designed by researchers functioned to encourage students to develop physical representation abilities, especially in light-reflecting material. Improved oral and written communication skills can be seen during the process as the results of student assignments and are shown by the results of the N-gain of 0,48 (medium category) and the paired t-test of Asymp. Sig (2-tailed) 0,000, therefore Asymp. A Sig (2-tailed) value below 0.05 indicates that Ho is rejected and H1 is accepted. This research can be innovative and used by teachers in the online learning process.